(untitled) (Research, Society and Development, 2022)
Promoting Environmental Education (EE) in times of a pandemic along with educational practices supports citizen training, demystifying pedagogical knowledge in both formal and non-formal environments. Thus, the present article addressed the use of the Pedagogical Workshop for the production of organic fertilizer and alternative teaching resources from the treatment and recycling of domestic solid waste, having as a differential the insertion of Digital Technologies in the period of Emergency Remote Teaching. Methodologically, the research had a qualitative-quantitative and experimental character. The results showed that the workshops achieved their objectives, effectively contributing to the promotion of EE, allowing, in addition to critical and reflective discussion about the environmental reality, allowing learning in the practice of disposal and reuse of solid waste. Therefore, the academic actions were sustainable, feasible and punctual in this research.